Harga Pokok Produksi Dalam Menentukan Harga Jual Melalui Metode Cost Plus Pricing Dengan Pendekatan Full Costing - Dian Purnama; Saiful Muchlis; Andi Wawo (JRAK: Journal of Accounting Research and Computerized Accounting, 2019)
The purpose of this study is to determine the calculation of the cost of production and selling price setting process at PT. Istiqamah Prima Sejahtera. Calculating the cost of production for the full costing method and setting the selling price using a cost plus pricing. This type of research is quantitative research. Based on the characteristics of the issues raised by the researchers, the study is classified as a quantitative descriptive research. The data used in this study are primary data obtained directly from the company such as data from interviews with the company and the data contains information on the production costs of companies during the month of September 2016. As for the secondary data obtained from books, journals, internet or other media which supported this research. From the analysis of the data, the results showed that the company's calculation of the cost of production is lower than the production cost price calculation using a full costing method. Cost of production is calculated using a method that is equal Rp85.472 company and according to the full costing method that is equal to Rp85.962. This is because in the calculation of factory overhead cost companies do not take into account some costs into the cost of production as the cost of maintenance and maintenance of production equipment, and the cost of depreciation on a shredded fish product. In addition, setting the selling price of the company only to estimate the selling price calculations per kg of shredded fish with a mark-up rate of 40%, amounting to Rp120,000 to set the selling price on the packaging of 100 grams, 250 grams and 500 grams. While using the cost plus pricing method with a mark up of 40% lower than the selling price according to the company in the amount of USD 12 683. (100 grams), Rp 30,488 (250 grams), and USD 60 798 (500 grams). So, setting the selling price should be done precisely because the price is too high will make the product less competitive, while the sale price is too low will lead to losses for the company.